2017
DOI: 10.1021/acs.energyfuels.7b00455
|View full text |Cite
|
Sign up to set email alerts
|

Nanofluid Enhanced Oil Recovery Using Hydrophobically Associative Zwitterionic Polymer-Coated Silica Nanoparticles

Abstract: Intense interest has been shown in the development of “smart nanofluids” because they can dramatically change their flow properties in complex fluid systems. We introduce a robust and straightforward approach to develop a smart nanofluid system, in which associative silica nanoparticles (ASNPs) were incorporated to regulate their flow properties in rock pores. ASNPs were synthesized by covalently coating a hydrophobically associative hygroscopic zwitterionic poly­[2-methacryloyloxyethyl phosphorylcholine (MPC)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
46
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 98 publications
(46 citation statements)
references
References 31 publications
(31 reference statements)
0
46
0
Order By: Relevance
“…The authors reported an incremental oil recovery up to 5.2% of OOIP after water flood. Like Choi, et al [30], they reported pressure decrease with NPs injection. The oil recovery was attributed to the interfacial tension reduction and wettability alteration to more waterwet condition.…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…The authors reported an incremental oil recovery up to 5.2% of OOIP after water flood. Like Choi, et al [30], they reported pressure decrease with NPs injection. The oil recovery was attributed to the interfacial tension reduction and wettability alteration to more waterwet condition.…”
Section: Introductionmentioning
confidence: 80%
“…Behzadi and Mohammadi [29] reported that polymer-coated silica NPs can modulate oil and water IFT and change the wettability of the oil-wet glass micromodel to more waterwet, resulting in higher EOR than unmodified silica nanoparticles. Experiments conducted by Choi, et al [30] found that, when injecting polymer-coated silica NPs into water-wet sandstones, 74.1% oil was recovered, which was comparable to water flood (68.9%) and 72.7% of OOIP from unmodified NPs. The authors argued that modified silica NPs increased oil recovery by lowering the injection pressure relative to unmodified ones, which was associated to the ordering of NPs in the wedge film between oil and rock surface, rendering more hydrophilic surface.…”
Section: Introductionmentioning
confidence: 95%
“…The effect of nanoparticles is lessened at surfactant concentrations greater than the CMC. The use of surfactant blends and composite particles (polymer-coated particles) to enhance oil film displacement have also been considered but such mechanisms are considered outside the scope of this paper [74,75]. Recent studies, which have considered composite fluids (particles), have been summarized in Table A3.…”
Section: Nanoparticle Oil Droplet Displacementmentioning
confidence: 99%
“…For decades, polymers are known as viscosity enhancer and have shown promising results, but present various challenges in oil field such as thermal instability, adsorption, gelation, high cost and environmental concern (Rellegadla et al 2017;Speight 2016). However, recent EOR studies focus on nanoparticles (NPs) utilization to improve important properties such as interfacial tension, wettability alteration and viscosity due to their thermophysical properties (Koca et al 2017;Adenutsi et al 2018;Zallaghi et al 2018;Sharma and Sangwai 2017;Choi et al 2017;Kean Chuan et al 2016;Cheraghian et al 2015;Pozhar 2000;Hendraningrat et al 2013). Worthen et al (2013) describe the advantage of NPs in surfactant blends for their ability to be irreversibly adsorbed at interface and provide potential benefits to surfactant's properties.…”
Section: Introductionmentioning
confidence: 99%